Selection of economic cross-section of precast reinforced concrete purlins - Goleš Danica; Varju Đerđ; Vajda Oliver (Zbornik Radova Građevinskog Fakulteta, 2017)
The selection of the cross section of precast reinforced concrete (RC) purlins is performed in the function of their span and load, while the spacing of these elements is chosen according to the bearing capacity and deformability of the roof cover. This paper presents an analysis of the consumption and price of the materials for the production of precast RC purlins of 6.0 m span for different spacing, shapes and dimensions of the cross section, aiming to achieve the minimum total cost of materials for production of the purlins of a two-bay hall, with meeting the requirements of resistance, service-ability and durability.